OUTLOOK FOR TAPIS FABRIC AS TRADITIONAL CRAFTS LAMPUNG SOCIETY IN THE INDICATION GEOGRAPHY LEGAL PROTECTION - Erlina B; Recca Ayu Hapsari; Risti Dwi Ramasari (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Tapis fabric as handicrafts depicting unique aspects of Lampung community life should receive other legal protection potential of more prospective and protect from the action claiming another country. Researchers assessed their registration tapis tradition of Lampung as a geographical indication products, be a potential for prevention as well as a norm that protects local names (geographical location), as a sign to recognize the quality or characteristic of the product.